Co-infections in tropics. Rare or Underreported? - Vijayakanthi, Nandini; Bhatt, Girish Chandra; Saha, Abhijeet (Asian Journal of Clinical Pediatrics and Neonatology, 2013)
Concurrent infection with two infectious agents can result in an illness having overlapping symptoms, resulting in a situation where both diagnosis and treatment of a patient may become difficult for a physician and misdiagnosis in a treatable systemic disease with liver involvement such as typhoid can have fatal consequences.